Reliability Analysis of Reinforced Concrete Beams in Lecture Buildings - Hasyim, Wachid (Gema Wiralodra, 2025)
During its service life, a building structure must be capable of withstanding the applied forces, which refers to its structural capacity. Beyond capacity, the structure must also be evaluated in terms of its probability of failure under loading conditions, a concept known as structural reliability. This study aims to analyze the reliability of reinforced concrete beam elements in buildings functioning as lecture facilities. The First Order Second Moment (FOSM) method was selected due to its effectiveness in incorporating statistical uncertainty into structural analysis, particularly for engineering problems involving variability in loads and resistance. The research was conducted through numerical analysis, which involved several key stages: (1) determining internal forces (bending and shear) from structural analysis, (2) collecting and assigning statistical parameters—namely, the mean and standard deviation—of dead loads, live loads, and material resistance, and (3) computing the reliability index for each beam element using the FOSM approach. The input data were derived from structural design specifications and relevant statistical references for load and material properties. The analysis results show that the maximum flexural reliability index values for beams B1, B2, RB, and SL are 8.29, 7.92, 7.62, and 8.34, respectively, while the maximum shear reliability index values are 3.96, 3.80, 4.29, and 4.28. All calculated values exceed the target reliability indices of 3.75 for new buildings and 2.75 for existing buildings, both for flexural and shear capacities. These findings indicate that the structural reliability of the analyzed beams is within a high and acceptable safety range.